2015
DOI: 10.1371/journal.pone.0127329
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Sensitizes TRAIL-Induced Hepatocyte Apoptosis by Inhibiting the E3 Ubiquitin Ligase A20

Abstract: Hepatitis B virus (HBV) infection causes hepatocyte death and liver damage, which may eventually lead to cirrhosis and liver cancer. Hepatitis B virus X protein (HBx) is a key antigen that is critically involved in HBV-associated liver diseases. However, the molecular basis for its pathogenesis, particularly in liver damage, has not been well defined. Herein, we report that HBx was able to enhance the susceptibility of hepatocytes to TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis. Increased se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Our present data showed that in TRAIL‐sensitive cells, Cbl‐b and c‐Cbl, the critical adaptors linking DR5 and TRAF2, were expressed at a low level. Previous studies reported that the hepatitis B virus X protein enhanced the sensitivity of hepatocytes to TRAIL by upregulation of miR‐125a targeting TNFAIP3 to enhance the activation of caspase‐8 (Zhang et al ., 2015b). Because our present data showed no changes in Cbl‐b and c‐Cbl mRNA in TRAIL‐sensitive and TRAIL‐resistant gastric cancer cells, we performed Affymetrix miRNA chip analyses to identify potential miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our present data showed that in TRAIL‐sensitive cells, Cbl‐b and c‐Cbl, the critical adaptors linking DR5 and TRAF2, were expressed at a low level. Previous studies reported that the hepatitis B virus X protein enhanced the sensitivity of hepatocytes to TRAIL by upregulation of miR‐125a targeting TNFAIP3 to enhance the activation of caspase‐8 (Zhang et al ., 2015b). Because our present data showed no changes in Cbl‐b and c‐Cbl mRNA in TRAIL‐sensitive and TRAIL‐resistant gastric cancer cells, we performed Affymetrix miRNA chip analyses to identify potential miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of A20 may affect the progress of HBV infection and liver diseases. For instance, HBV X protein (HBx) was indicated to be able to affect the expression of A20 and promote TNF-related apoptosis-inducing ligand (TRAIL)-induced hepatocyte apoptosis [ 11 ]. A20 mRNA expression in peripheral blood mononuclear cells was shown to be associated with progression of chronic HBV infection [ 12 ], and increased A20 expression on monocytes was shown to be associated with the severity of acute-on-chronic liver failure related to HBV infection [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al . showed that hepatitis B virus X protein (HBx) sensitizes TNF‐related apoptosis‐inducing ligand (TRAIL)‐induced hepatocyte apoptosis by inhibiting A20 at the protein but not the mRNA level via upregulation of miR‐125a. Thus, further research is necessary to elucidate whether HBV proteins have any impact upon the expression of A20 protein.…”
Section: Discussionmentioning
confidence: 99%